The Influence of Compensation and Work Discipline on Employee Performance at PT Pacific Indah Pratama - Aditya, Rizky; Yuningsih, Erni; Kartini, Tini (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
Human resource development and coaching is one of the right efforts to deal with a company's problems or challenges related to strategic environmental changes. This study aims to determine the effect of compensation and work discipline on employee performance at PT. Pacific Indah Pratama employees. The sample in this study was 81 people using saturated sampling techniques. The analysis method used is descriptive and verification methods. Data collection techniques through questionnaires, observations, interviews and literature studies. The data analysis used is multiple linear regression analysis. The results of this study areCompensation and work discipline have a positive and significant influence on employee performance